The association of common autoimmune diseases with autoimmune thyroiditis: a two-sample Mendelian randomization study - Zhang, Kaiyuan; Luo, Ziyue; Wang, Xinchang (Frontiers in Endocrinology, 2024)
Objective: Numerous observational and retrospective studies have demonstrated an association between Autoimmune Thyroiditis (AIT) and various systemic Autoimmune Diseases (AIDs). However, the causal relationship between them remains uncertain. This study aims to investigate the causal link between AIT and diverse types of AIDs utilizing the Mendelian Randomization (MR) method.We assessed the causal relationship between AIT and eight prevalent AIDs. Summary statistics from genome-wide association studies (GWAS) were sourced from the FinnGen biobank and IEU Open GWAS database. Two-sample MR analyses were conducted, with the primary statistical approach being the Inverse Variance Weighting (IVW) method. This was complemented by a series of sensitivity analyses, and the robustness of the findings was evaluated through the estimation of heterogeneity and pleiotropy.When AIT was considered as the outcome, MR evidence suggested an association between Rheumatoid arthritis (RA), Type 1 diabetes (T1D), and Systemic lupus erythematosus (SLE) with AIT.Utilizing the Inverse Variance Weighting (IVW) method, we observed an increased risk of AIT with exposure to RA (P = 0.024, OR=1.25; 95% CI = 1.03, 1.52), T1D (P < 0.001, OR=1.27 95% CI = 1.11,1.46), and SLE (P = 0.037, OR=1.14; 95% CI = 1.04,1.26). Conversely, no significant genetic causal relationship with AIT was found for Sjögren's syndrome (SS), Ankylosing Spondylitis (AS), Multiple sclerosis (MS), Crohn's disease (CD), and Ulcerative colitis (UC).This study identified RA, T1D, and SLE as triggering factors for AIT. The incidence rate of AIT in patients with RA, T1D, and SLE may be higher than that in the general population. Therefore, individuals with these three diseases should undergo regular monitoring of thyroid-related indicators.